DETERMINAN KINERJA KEUANGAN DESA DI KECAMATAN RANTAU KABUPATEN ACEH TAMIANG - Reiky Andika; Afrah Junita; Muhammad Salman (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This study aims to determine the effect of leadership style, discipline, motivation and organizational commitment on the financial performance of village governments in Rantau District, Aceh Tamiang District. The sample in this study amounted to 96 respondents. The data analysis method used is multiple linear regression analysis, t test, F test, and coefficient of determination test. The results of the study partially show that leadership style, discipline, motivation, and organizational commitment have a significant effect on the financial performance of village governments in Rantau District, Aceh Tamiang Regency. Simultaneously leadership style, discipline, motivation, and organizational commitment simultaneously have a significant effect on the financial performance of village governments in Rantau District, Aceh Tamiang Regency. The limitation of this research is that the sample is only taken from the secretaries and hamlet heads, so that they are not fully represented. In addition, in collecting data, researchers only use the questionnaire method, so they will not get answers that are more reflective of the actual situation. Suggestions for future researchers to expand this research by adding other variables such as work culture and organizational communication. In addition, it is also expected to increase the number of respondents and use the interview method, because with the interview method the researcher will get answers that are more reflective of the actual situation.